A flexible job shop scheduling approach with operators for coal export terminals. (April 2019) - Burdett, Robert L.; Corry, Paul; Yarlagadda, Prasad K.D.V.; Eustace, Colin; Smith, Simon
Highlights: A new approach for scheduling and resourcing activities of coal export terminals is proposed. The CET is modelled as a flexible job shop with operators and solved via advanced meta-heuristics. A key ingredient of the optimisation process is the application of a priority ordering chromosome. Real life test problems are solved and numerical investigations demonstrate an effective approach. Abstract: Operating a coal export terminal (CET) is a challenging task. The throughput of the terminal and the delays incurred by ships and trains is greatly affected by where material is stacked and reclaimed, and which machinery is used to perform those tasks. To improve the operation of these terminals, and to make the aforementioned decisions, a novel optimisation approach has been developed. In that approach the CET is modelled as a flexible job shop with operators (FJSOP). The optimization problem is then solved using an advanced meta-heuristic algorithm that incorporates a variety of sophisticated perturbation techniques, local improvement algorithms and pre-emption handling procedures. That level of intricacy is rarely required for more traditional scheduling problems but is a necessity for this one. A key component used in the optimisation process is a priority ordering of the activities. The priority ordering is used to create the required activity sequences, for each piece of machinery. This list dictates the order in which activities are scheduled and can be perturbed quickly and in many different ways, leading to the identification of improved solutions. The optimization approach is applied to an Australian coal terminal to demonstrate its viability and effectiveness. Numerical testing shows that problems of the size encountered by existing terminals can be handled and high quality solutions can be obtained with reasonable computing effort.